(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
For human development and growth as a complete person, all its members must function healthily and fully. Unfortunately, not all people are healthy in all respects. Despite this, people with various disabilities also strive for perfection. We can safely include blind people in this group.